The Science in Adaptive Management - Ripley, Matt; Jaccard, Sabine (ILO, 2016)
‘Adaptive management’ is all the rage in international development circles. But to avoid yet another buzzword – we need to learn from the experience of natural resource science.
Keywords: IMPORTANT

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume I: Evaluation Report - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Sida, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume II: Case studies - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Sida, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

Monitoring and Result Measurement for Adaptive Programming - How to Use Data to Manage a MSD Program: Lessons from PRISMA - Khan, Khaled; Seely, Kevin; Ridwan, Mustika; Mulya, Bodhiya (PRISMA, 2019)
Using monitoring data to improve interventions is harder than it seems. Decision-makers are often busy implementing activities, unclear about their roles in data collection and analysis, and uncertain what data matters most or when. PRISMA, an AUD77 million agricultural Market Systems Development (MSD) programme funded by DFAT Australia, has encountered these challenges. With the programme completing its first five year phase, this case study shares ten key lessons divided into three sections: shaping the culture, developing systems, and top management decisions. These lessons aim to help program, sector and intervention managers make better use of monitoring data to improve interventions.

Building a team culture for Adaptive Management in MSD: 5 Strategies MEL Managers Say Work - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (USAID, 2023)
Keywords: Bolder Meghan; Gover Dun; Henao Lina; Nasution Zulka; Okutu David

Enhancing partner and system-level learning: 8 Tips from MEL Managers - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (USAID, 2023)
Effective learning is a key driver of market systems change, with the potential to enhance system competitiveness, resilience, and inclusiveness. Shifting the Locus of Learning: Catalyzing Private Sector Learning to Drive Systemic Change recently outlined a rationale for enhancing the scale and quality of learning in a system and identifying 10 strategies programs can contextualize to catalyze learning. These strategies are also backed with robust examples from 13 programs doing this work across 11 countries. To deepen insights on what MSD Monitoring, Evaluation and Learning (MEL) Managers have experienced in putting several of those strategies into practice, the Feed the Future Market Systems and Partnerships (MSP) Activity convened a series of peer discussions as part of a larger initiative (see Figure 1). This brief shares the collective learning and experience on this topic of three senior MEL Managers who were interested in and had experience with this topic. The group represented full-time, program-based MEL Leads working on MSD programs funded by USAID and DFAT, based in Fiji, Albania, and Kosovo working for Adam Smith International, SwissContact, and DT Global, respectively. From those discussions, this paper synthesizes eight tips from MEL Managers for practically enhancing partner and system-level learning: 1. Identify the right decision-maker(s) at potential partners. 2. Use a co-creation process to identify learning opportunities. 3. Use diagnostics and assessments to strengthen partner and system capacity for actionable learning. 4. Use a phased capacity strengthening process tied to behavior change. 5. Measure partners’ continued investment in and use of learning—not the continuation of specific learning activities. 6. Work with sector-level institutions for scale but be aware of risks. 7. Leverage informal communities of practice to share learning. 8. Use the right terminology to talk about partner and system-focused learning.

A Systems Framework for International Development: The Data-Layered Causal Loop Diagram - Blair, Courtney; Gralla, Erica; Wetmore, Finley; Goentzel, Jarrod; Peters, Megan (Production and Operations Management, 2021)
Meeting the United Nations Sustainable Development Goals (SDGs) will require adapting or redirecting a variety of very complex global and local human systems. It is essential that development scholars and practitioners have tools to understand the dynamics of these systems and the key drivers of their behavior, such as barriers to progress and leverage points for driving sustainable change. System dynamics tools are well suited to address this challenge, but they must first be adapted for the data-poor and fragmented environment of development work. Our key contribution is to extend the causal loop diagram (CLD) with a data layer that describes the status of and change in each variable based on available data. By testing dynamic hypotheses against the system's actual behavior, it enables analysis of a system's dynamics and behavioral drivers without simulation. The data-layered CLD was developed through a 4-year engagement with USAID/Uganda. Its contributions are illustrated through an application to agricultural financing in Uganda. Our analysis identified a lack of demand for agricultural loans as a major barrier to broadening agricultural financing, partially refuting an existing hypothesis that access to credit was the main constraint. Our work extends system dynamics theory to meet the challenges of this practice environment, enabling analysis of the complex dynamics that are crucial to achieving the SDGs.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/poms.13492